O espaço físico de uma instituição de Educação Infantil: como as crianças significam esse lugar? - Souza, Aline Constância de Figueiredo e (2020)
This master's research aimed to investigate and analyze how children perceive the physical spaces of an early childhood education institution and the meanings they give to this place. It is assumed that the physical space in the institutions of Early Childhood Education plays a fundamental role in the educational process, in the quality of the experiences and interactions afforded to children. The concepts of space and place were central to the process of this research. We start from understanding the term space as the characteristics of the physical structure itself, what can be touched, felt, seen, lived, measured and explored. The term place, on the other hand, is understood as a qualitative leap, constituted from the senses and meanings given by the subjects to the spaces through the relationships lived with / in the space. Thus, we consider that the meanings that children give to the spaces of the children's institution that they attend daily transforms these spaces into places and can collaborate to qualify these spaces. It is a research with a qualitative research approach, with ethnographic inspiration. We also use theoreticalmethodological inputs that guide the deepening of knowledge about conducting research with the direct participation of children as active collaborators in the construction of data. In the search for children's meanings, we approach the theory of subjectivity developed by González Rey, which has a cultural-historical perspective and proposes the constructive-interpretative methodology which we understand as a contribution that helps to achieve a better understanding from the children's point of view. We defined as the empirical field the Municipal Center for Early Childhood Education Castro Alves, in Salvador / BA and as subjects of the research, at first, all the children of the institution and in a second moment, thirty-two children between four and six years of age. For the construction of the data, the following procedures were used: observation, photographic records, records written in a field diary, semi-structured interview with the drawing of drawings by the 32 children subject to research and documentary analysis of official Brazilian documents and the Political Project Pedagogical Committee of the CMEI. The data were organized into two major categories considering the set of meanings attributed by the children: preferred spaces and deprecated spaces. The research findings showed that for children, the preferred spaces of CMEI were meant as places to be together, to play, to explore, to appreciate and to learn. In addition, unsightly spaces that are unpleasant to the senses and spaces and equipment that are inappropriate to use and that hinder play were the places identified as neglected by children from these meanings printed by them. The children's gestures, drawings and speech indicate aspects that often go unnoticed by adults, highlighting the importance of hearing, seeing, perceiving and feeling children in the educational routine and, above all, in research that addresses issues related to day-to-day activities of early childhood education institutions. We conclude that the CMEI spaces have many inadequacies, and do not, in general, meet what the official Brazilian documents highlight on this issue. However, we recognize that CMEI's children are happy in this place and that there is a quest to respect their particularities. They interact with children, teachers and other adults in a meaningful and dynamic way. They play, learn, grow and develop in a pleasant way. We have the expectation that the participation, so committed and valued, of the children of CMEI in this research, may in fact open the way so that, in early childhood education institutions, children's perspectives are taken into account in the constitution of educational spaces.